Creativity Improvement of Karang Taruna at Jagakarsa Village through the Utilization of Youtube Channel - Anggun Citra Dini Dwi Puspitasari; Zetty Karyati; Rahmawati Rahmawati (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2022)
The purpose of this community service activity is to provide socialization about the use of Youtube as a medium for improving youth’s creativity so that they are active and creative in making events and activities in their environment. From the implementation of this community service, it is hoped that it can spark enthusiasm of Jagakarsa Karang Taruna’s members to develop their creativity in creating events and activities in their village. This community service was carried out at Karang Taruna RT 002 RW 03 Jagakarsa Village, Jagakarsa District, South Jakarta. The result of this community service activity is that the members of this Karang Taruna are able to edit their video documentation so that it is ready to be published on their Youtube channel Karang Taruna RT 02 RW 03 Jagakarsa.